1999
DOI: 10.1034/j.1399-3003.1999.14a32.x
|View full text |Cite
|
Sign up to set email alerts
|

Tongue protrusion force and fatiguability in male and female subjects

Abstract: Limb and respiratory muscle (diaphragm) strength and fatiguability have been extensively studied in man and are known to vary with age and sex. However, in contrast to limb muscles and the diaphragm, force and fatiguability characteristics have not been studied in upper airway muscles. This study examines the hypotheses that tongue protrusion strength or fatiguability, determined by the properties of the intrinsic muscles and genioglossus, may change with age and may be reduced in males compared to females. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
60
3
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 23 publications
12
60
3
2
Order By: Relevance
“…Os instrumentos que utilizam extensômetros [3][4][5][6][7][8][9] geralmente apresentam uma estrutura mecânica pesada, necessária para seu funcionamento e também possuem estruturas dos sensores pouco flexíveis, o que pode causar feridas ou desconforto ao paciente. Outro problema específico, já ocorrido na literatura 3 é a falta de uma peça que faça a interface entre a língua e o transdutor, sendo então possível medir apenas a pressão de contato da língua e não a pressão total da língua.…”
Section: Figura 4 -Dispositivos Que Empregam Outras Tecnologiasunclassified
“…Os instrumentos que utilizam extensômetros [3][4][5][6][7][8][9] geralmente apresentam uma estrutura mecânica pesada, necessária para seu funcionamento e também possuem estruturas dos sensores pouco flexíveis, o que pode causar feridas ou desconforto ao paciente. Outro problema específico, já ocorrido na literatura 3 é a falta de uma peça que faça a interface entre a língua e o transdutor, sendo então possível medir apenas a pressão de contato da língua e não a pressão total da língua.…”
Section: Figura 4 -Dispositivos Que Empregam Outras Tecnologiasunclassified
“…In the literature, some studies have found a relationship between increasing of age and decreasing of tongue force (2,(14)(15)(16)18) . However, the strength reduction only occurs after age 60 (12)(13)(14) justifying the non stratification of the sample by age.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum force of the tongue in normal individuals has been documented by several studies (2)(3)(4)(5) . In some studies this force is measured by means of the movement of protrusion against resistance (2,(6)(7)(8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations